Influence of bio-lubricants on the orthodontic friction. (July 2016) - Dridi, A.; Bensalah, W.; Mezlini, S.; Tobji, S.; Zidi, M.
Abstract: The Friction force of Stainless Steel (SS) and Nickel–Titanium (Ni–Ti) rectangular archwires against stainless steel brackets was investigated. Two types of brackets were used namely: Self-ligating brackets (SLB) and conventional brackets (CB). The friction tests were conducted on an adequate developed device under dry and lubricated conditions. Human saliva, olive oil, Aloe Vera oil, sesame oil and sunflower oil were used as bio-lubricants. The friction force was examined as a function of the ligation method and oil temperature. It is found that under oil lubrication, the friction behavior in the archwire/bracket assembly were the best. The SLB ligation was better than the conventional ligation system. The enhancement of the frictional behavior with natural oils was linked to their main components: fatty acids. Highlights: We study the effect of bio lubricants on the orthodontic friction. Natural oils reduced remarkably the frictional force. Natural oils decrease the friction force due to their fatty acids content. Fatty acids formed a lubrication layer between the archwire/bracket surfaces.